(untitled) (Research, Society and Development, 2020)
Pterodon pubescens (Benth.) Benth is native species from the Brazilian Cerrado, popularly known as “sucupira-branca,” and rich in bioactive metabolites. This study aimed to assess the inhibitory activity of the enzyme acetylcholinesterase by leaf extracts of P. pubescens Benth. Phenolic constituents and flavonoids were analyzed by LC-DAD and LCMS. The qualitative and quantitative enzymatic inhibitory profile was performed by 96-well microplate in ELISA reader. The statistical analysis was reached with a significance limit of p < 0.05 applied by the Tukey’s test. Bioactive components detected were terpenoids, phenolic acids (gallic acid, ferulic acid, and rosmarinic acid), and flavonoids (kaempferol, luteolin, apigenin, rutin, and quercetin). There were no significant differences of inhibition between the crude methanolic and ethyl acetate extracts and between the hydroalcoholic and ethyl acetate phases at the concentration of 80 µg mL-1. The phytochemical profile in LCMS are related to the acetylcholinesterase inhibitory effect. This species has an importance for future in vivo studies, purification, and isolation of molecules with a possible biopesticidal effect.